2019
DOI: 10.2147/ndt.s234813
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exploration of Treatment-Resistant Schizophrenia Subtypes Based on a Survey of 204 US Psychiatrists</p>

Abstract: ObjectiveTo explore and describe potential subgroups within the treatment-resistant schizophrenia (TRS) population, using data from a survey of US psychiatrists.MethodsPsychiatrists completed an online survey of demographic/clinical characteristics and treatment history for two of their patients with TRS. Patients were stratified according to number of suicide attempts, number of hospitalizations, employment status, and TRS onset time frame.ResultsOf the 408 patients with TRS described by psychiatrists, 37.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
7
1
Order By: Relevance
“…Also, these data do not differ from previous report on the medical profile for TRS patients. 52 , 53 We found a mean clozapine dose of 266 mg/day (SD ±135), and our outcomes are consistent with other reports. 54 , 55 Thus, although our sample is small, it appears to be representative of the TRS population reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Also, these data do not differ from previous report on the medical profile for TRS patients. 52 , 53 We found a mean clozapine dose of 266 mg/day (SD ±135), and our outcomes are consistent with other reports. 54 , 55 Thus, although our sample is small, it appears to be representative of the TRS population reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…These findings extend those of a previous study reporting that cognitive deficits are more deficient in NRTT than in PRTT and are associated with clinical symptoms (32). This greater neurocognitive burden in TRS associated with greater illness severity suggests that there is a continuum or dimensional gradient from non-TRS to mild-TRS and the more severe forms of TRS (33). Nevertheless, some other studies attempted to define TRS as a qualitatively different class as in a systemic review of 19 studies which concluded that based on biomarker research including glutamatergic, but no dopaminergic aberrations, reduced grey matter and a higher familial load there is tentative evidence to conceptualize TRS as a qualitatively different class to non-TRS (34).…”
Section: Discussionsupporting
confidence: 85%
“…There is one main difference between our study and previous research on early/late TRS (Ajnakina et al, 2020;Correll et al, 2019;Demjaha et al, 2017;Lally et al, 2016). Previous studies focused on investigating predictors of early, or late, onset of TRS compared to the non-development of TRS; while our study focused exclusively on exploring if there are sociodemographic and clinical factors related to the length of treatment in a cohort of cases of TRS.…”
Section: Discussionmentioning
confidence: 96%